Fine-grained description model and implementation of hypermedia document - Mang SU; Guo-zhen SHI; Feng-hua LI; Ying SHEN; Qiong HUANG; Miao-miao WANG (Tongxin xuebao)
According to the tendency of development for digital media convergence and management of massive data, a fine-grained hypermedia document description model and its implementation were proposed, basing the analysis of the relationship between the related multidimensional digital media. The method for access control was given, as well as its XML description grammar system. The model could satisfy the demands of convenient and effective management.